Upaya Peningkatan Kemampuan Perawat dalam Pemberdayaan Keluarga untuk Meningkatkan Ketahanan Keluarga Orang dengan Skizofrenia (ODS) di Kota Padang - Dewi Eka Putri; Rika Sarfika; Feri Fernandes; Bunga Permata Wenny; Rika Sabri; Gusti Sumarsih (Warta Pengabdian Andalas, 2023)
People living with schizophrenia in West Sumatra are currently experiencing an increase. In 2018 the prevalence of schizophrenia reached 9 per 1000 households. This prevalence is above the national average. The problem that often occurs in people with schizophrenia (ODS) is relapse. High relapse also occurs in ODS in Padang. It was because of non-compliance with treatment and a lack of support from the family. Inadequate support is the impact of the low resilience of the ODS family. Therefore, the purpose of this community service is to increase the ability of nurses to empower families to increase family resilience so that ODS relapse is low. The method used in this community service is the provision of training. The training was given to 14 nurses holding mental programs at the Padang City Health Centers. The training was carried out for three days at the Faculty of Nursing Unand Padang. Community service resulted in nurses' knowledge in empowering ODS families before training was an average of 50.75, and nurses' knowledge after training was an average of 62.78, increasing by 12.03 points. It hopes that nurses could empower ODS families through home visits so that every ODS family member has the knowledge and ability to care for ODS so that family resilience increases and relapse can prevent.